Landscape patterns influence communities of medium- to large-bodied vertebrates in undisturbed terra firme forests of French Guiana. (September 2015) - Richard-Hansen, Cécile; Jaouen, Gaëlle; Denis, Thomas; Brunaux, Olivier; Marcon, Eric; Guitet, Stéphane
Abstract: Whereas broad-scale Amazonian forest types have been shown to influence the structure of the communities of medium- to large-bodied vertebrates, their natural heterogeneity at smaller scale or within the terra firme forests remains poorly described and understood. Diversity indices of such communities and the relative abundance of the 21 most commonly observed species were compared from standardized line-transect data across 25 study sites distributed in undisturbed forests in French Guiana. We first assessed the relevance of a forest typology based on geomorphological landscapes to explain the observed heterogeneity. As previously found for tree beta-diversity patterns, this new typology proved to be a non-negligible factor underlying the beta diversity of the communities of medium- to large bodied vertebrates in French Guianan terra firme forests. Although the species studied are almost ubiquitous across the region, they exhibited habitat preferences through significant variation in abundance and in their association index with the different landscape types. As terra firme forests represent more than 90% of the Amazon basin, characterizing their heterogeneity – including faunal communities – is a major challenge in neotropical forest ecology.